New insights for the regulatory feedback loop between type 1 crustacean female sex hormone (CFSH-1) and insulin-like androgenic gland hormone (IAG) in the Chinese mitten crab (Eriocheir sinensis) - Zhu, Dandan; Feng, Tianyi; Mo, Nan; Han, Rui; Lu, Wentao; Shao, Shucheng; Cui, Zhaoxia (Frontiers in Physiology, 2022)
To clarify the hormone control on sex determination and differentiation, we studied the Chinese mitten crab, Eriocheir sinensis (Henri Milne Edwards, 1854), a species with importantly economic and ecological significance. The crustacean female sex hormone (CFSH) and the insulin-like androgenic gland hormone (IAG) have been found to be related to the sex determination and/or differentiation. CFSH-1 of E. sinensis (EsCFSH-1) encoded a 227 amino-acid protein including a signal peptide, a CFSH-precursor-related peptide, and a mature CFSH peptide. Normally, EsCFSH-1 was highly expressed in the eyestalk ganglion of adult female crabs, while the expression was declined in the intersex crabs (genetic females). The intersex crabs had the androgenic glands, and the expression level of EsIAG was close to that of male crabs. During the embryogenesis and larval development, the changes of EsCFSH-1 and EsIAG genes expression in male and female individuals were shown after the zoea IV stage. Next, we confirmed the existence of the regulatory feedback loop between EsCFSH-1 and EsIAG by RNA interference experiment. The feminization function of EsCFSH-1 was further verified by examining the morphological change of external reproductive organs after EsCFSH-1 knockdown. The findings of this study reveal that the regulatory interplay between CFSH and IAG might play a pivotal role in the process of sex determination and/or differentiation in decapod crustaceans.